Intravesical Botulinum Toxin for Persistent Autonomic Dysreflexia in a Pediatric Patient. (23rd February 2016) - Lockwood, Gina; Durkee, Charles; Groth, Travis
Abstract : Introduction . We present a novel case of persistent autonomic dysreflexia in a pediatric spinal cord injury patient treated successfully with intravesical botulinum toxin. Study Design . A retrospective chart review of one patient seen at the Children's Hospital of Wisconsin from 2006 to 2012 was performed. Results . A pediatric spinal cord injury patient with known neurogenic bladder presented with severe hypertension consistent with autonomic dysreflexia. His symptoms and hypertension did not improve with conservative measures, and he necessitated ICU admission and antihypertensive drips. He was taken to the operating room for intravesical botulinum toxin for refractory bladder spasms. Following this, his symptoms abated, and he was weaned off IV antihypertensives and returned to his baseline state. His symptoms were improved for greater than six months. Conclusions . There are few treatment options for the management of refractory autonomic dysreflexia. Intravesical botulinum toxin has never been reported for this use. Dedicated research is warranted to assess its efficacy, as it was used successfully to abort autonomic dysreflexia in this patient.